2022
DOI: 10.3855/jidc.15545
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of the Pfizer BioNTech vaccine in health workers of a hospital in the southeast of Mexico

Abstract: Introduction: The goal of this study was to evaluate the side effects of application of the Pfizer BioNTech vaccine on the workers at a Mexican hospital. Methodology: A cross-sectional study was carried out, in which 1351 workers from a tertiary care center in the Mexican southeast were included. Sociodemographic data, comorbidities, and side effects after the Pfizer BioNTech vaccine were obtained through an online survey. The variables were analyzed through descriptive statistics. The presence or absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Focusing on health care workers, vaccination appears highly effective and safe [15] . However, reports from around the globe mostly indicate rates of adverse events which are similar or even higher than in our cohort ranging from 77% in a collection from Mexico up to 98% in a cohort from the U.S. [16] , [17] , [18] , [19] with a substantial contribution of psychological and social effects triggered by the pandemic [20] . Interestingly, it could be reconfirmed that high rates of adverse events correlate with post-vaccination antibody levels [18] .…”
Section: Discussionsupporting
confidence: 60%
“…Focusing on health care workers, vaccination appears highly effective and safe [15] . However, reports from around the globe mostly indicate rates of adverse events which are similar or even higher than in our cohort ranging from 77% in a collection from Mexico up to 98% in a cohort from the U.S. [16] , [17] , [18] , [19] with a substantial contribution of psychological and social effects triggered by the pandemic [20] . Interestingly, it could be reconfirmed that high rates of adverse events correlate with post-vaccination antibody levels [18] .…”
Section: Discussionsupporting
confidence: 60%
“…While research from Mexico has reported common side effects (health-care workers) after Pfizer-BioNTech vaccine administration as pain at the vaccination site (76.7%), headache (32.9%), and fatigue (30.3%). [23]. The current research discovered that 2.2% of participants contracted the disease after the second dose of the COVID-19 vaccine and 3.4% after the first dose.…”
Section: Discussionmentioning
confidence: 68%
“…The prevalent vaccine type in the current study is Covishield, but most of the studies conducted around the world are based on, Sinopharm, Pfizer (BNT162b2), Moderna, CoronaVac, and various other vaccines [21][22][23][24][25]. Participants in the studies conducted in Uganda and Ethiopia were received the AstraZeneca vaccine; the current study's vaccine mixture was not used in those studies [26,27].…”
Section: Discussionmentioning
confidence: 99%